2020
DOI: 10.1038/s41598-020-67713-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of contrast-enhanced ultrasound for acute pyelonephritis in children

Abstract: The objective of our study was to evaluate the performance of renal contrast-enhanced ultrasound (CEUS) against the 99m-labeled dimercaptosuccinic acid (DMSA) scan and computed tomography (CT) in children for the diagnosis of acute pyelonephritis. We included children who underwent both renal CEUS and the DMSA scan or CT. A total of 33 children (21 males and 12 females, mean age 26 ± 36 months) were included. Using the DMSA scan as the reference standard, the sensitivity, specificity, positive predictive value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…Uropathogenic Escherichia coli (UPEC) is the commonest causative organism for both complicated and uncomplicated UTIs [ 5 , 6 , 7 , 8 ]. Undetected and untreated acute pyelonephritis may lead to renal hypertension, renal scarring, and even renal failure [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uropathogenic Escherichia coli (UPEC) is the commonest causative organism for both complicated and uncomplicated UTIs [ 5 , 6 , 7 , 8 ]. Undetected and untreated acute pyelonephritis may lead to renal hypertension, renal scarring, and even renal failure [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the annual cost of treating this disease in France and the US was about €58 million and $2.47 billion, respectively [ 2 , 3 ]. In childhood, this disease usually occurs in boy infants due to congenital anomalies of kidneys and urinary tract, while AP is observed in girls at older ages [ 4 6 ]. Escherichia coli is the main responsible pathogen for AP.…”
Section: Introductionmentioning
confidence: 99%
“…The renal scarring significantly develops the risk of hypertension, proteinuria, vesicoureteral reflux (VUR), chronic kidney disease, and end-stage renal disease [ 9 , 10 ]. Since renal scarring is observed in 37% of AP children after two years from the infection onset, the rapid diagnosis and implementation of effective therapeutic measures are necessary to manage this disease among children [ 4 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has beenreported that the annual cost to treat this disease in France and the US respectively was about €58 million and $2.47 billion [2,3]. In childhood, this disease commonly occurs in boy infants due to congenital anomalies of the kidneys and urinary tract, while AP is observed in girls at older ages [4][5][6]. Escherichia coli is the main responsible pathogen for AP, which is often associated with severe in ammation and short-term (such as fever, dysuria, and ank pain) and long-term (irreversible renal scarring (RS)) morbidities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The RS signi cantly accelerates the risk development of hypertension, proteinuria,vesicoureteral re ux (VUR), chronic kidney disease, and end-stage renal disease [9,10]. Since about 37% of children with AP after two years from the infection onset showed renal scarring, the rapid diagnosis and the implementation of effective therapeutic measures are necessary to manage this disease among children [4,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%